Rwanda 1994 The Myth of the Akazu Genocide Conspiracy and its Consequences - Collins, Barrie. (Rethinking Political Violence, 2014)
Through a rigorous critique of the dominant narrative of the Rwandan genocide, Collins provides an alternative argument to the debate situating the killings within a historically-specific context and drawing out a dynamic interplay between national and international actors.